Fundamental drivers of existing home sales in Canada - Taylor Webley (Bank of Canada, 2018)
Existing home sales' share of Canada's economic pie has been rising in recent years, and variation around this trend has resulted in outsized contributions to changes in real gross domestic product (GDP). In this context, we use a cointegration framework to estimate the level of resale activity across the Canadian provinces that is supported by fundamentals - namely, full-time employment, housing affordability and migration flows - to help look through the volatility. The results suggest that, over longer horizons, resales activity and these fundamentals share a stable relationship, although deviations are sometimes persistent. We also find a robust and positive relationship between house price growth and deviations of existing home sales from fundamentals. While predicting quarterly changes in resales remains very difficult, provincial models improve upon national and naïve benchmarks and provide a useful framework for identifying risks to GDP growth that stem directly from the resale market.
Keywords: C; C2; C22; C23; E; E2; E27; R; R2; R21; 330; Econometric and statistical methods; Economic models; Housing